Anna Maria's needleworks notebook - Horner, Anna Maria, 1972- (John Wiley & Sons Inc., 2012)
The book features four categories of needlework: cross stitch, needlepoint, embroidery, and crewel. Each category offers advice on common tools used, Anna Maria's favorite techniques, and hold-your-hand instruction on how to develop your own inspired patterns. In addition, each project journals her process right down to the precise fabrics and exact color number of every thread used in the beautifully photographed examples.